Temporal variability of the rove beetle (Coleoptera: Staphylinidae) community on small vertebrate carrion and its potential use for forensic entomology. (June 2021) - Weithmann, Sandra; von Hoermann, Christian; Degasperi, Gregor; Brandt, Katharina; Steiger, Sandra; Ayasse, Manfred
Abstract: Rove beetles (Coleoptera: Staphylinidae) are one of the most important colonizers of vertebrate cadavers. We have previously investigated carrion-associated rove beetle communities across various forests and demonstrated that the study regions are the main drivers of the local rove beetle species pool that is, in turn, able to colonize a carcass. Nevertheless, little is known about their temporal variation in community composition during the decomposition process. The aim of our study has been to analyze the temporal changes of the composition of the rove beetle community and to identify new, potentially useful candidate species for forensic entomological evaluations. We determined 80 rove beetle species that were attracted to 60 piglet cadavers across various forest stands in Germany. Both the abundance and the community composition changed over the decomposition process, independently of the species-specific geographical variation across study regions. In the region Schorfheide-Chorin, species from the genus Philonthus proved to be a suitable group for future forensic entomological investigations. They appeared in markedly high numbers at piglet cadavers from the bloated stage until the advanced decay stage. For the study region Schwäbische Alb, we newly describe the species Omalium septentrionis as a member of the carrion-associated rove beetle fauna. Based on the geographical variation in rove beetle community compositions, we have filtered out several species that might contribute to advances in postmortem interval estimations or other applied fields in forensic entomological contexts. Graphical Abstract: ga1 Highlights: Rove beetles (Staphylinidae) are underexplored in a forensic entomological context. Aim to test temporal change over decay and to identify species useful for forensics. 80 rove beetle species were determined on 60 piglet cadavers in various forests. Genus Philonthus was a post-bloating indicator group for small vertebrate carrion. Omalium septentrionis was a new member of the carrion-associated rove beetle fauna.